Detecting AGG Interruptions in Females With a FMR1 Premutation by Long-Read Single-Molecule Sequencing: A 1 Year Clinical Experience - Ardui, Simon; Race, Valerie; de Ravel, Thomy; Van Esch, Hilde; Devriendt, Koenraad; Matthijs, Gert; Vermeesch, Joris R. (Frontiers in Genetics, 2018)
The fragile X syndrome arises from the FMR1 CGG expansion of a premutation [55-200 repeats] to a full mutation allele [> 200 repeats] and is the most frequent cause of inherited X-linked intellectual disability. The risk for a premutation to expand to a full mutation allele depends on the repeat length and AGG triplets interrupting this repeat. In genetic counseling it is important to have information on both these parameters to provide an accurate risk estimate to women carrying a premutation allele and weighing up having children. For example, in case of a small risk a woman might opt for a natural pregnancy followed up by prenatal diagnosis while she might choose for preimplantation genetic diagnosis if the risk is high. Unfortunately, the detection of AGG interruptions was previously hampered by technical difficulties complicating their use in diagnostics. Therefore we recently developed, validated and implemented a new methodology which uses long-read single-molecule sequencing to identify AGG interruptions in females with a FMR1 premutation. Here we report on the assets of AGG interruption detection by sequencing and the impact of implementing the assay on genetic counseling.